2009
DOI: 10.1177/1933719109342280
|View full text |Cite
|
Sign up to set email alerts
|

Possible Gene-Gene Interaction of KIR2DL4 With its Cognate Ligand HLA-G in Modulating Risk for Preeclampsia

Abstract: Preeclampsia (PE) is a leading cause of maternal and fetal mortality and morbidity that occurs only during pregnancy. Pregnancy is the only physiological situation where killer-cell immunoglobulin-like receptors (KIRs) may meet cognate nonself variants of human leukocyte antigen (HLA) allotypes. We previously reported that presence of fetal HLA-G*0106 was significantly associated with risk for PE in multigravid pregnancies. We have now tested the KIR2DL4 receptor gene for association with PE, as well as for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…Although it is very unlikely that this amino acid substitution changes the overall conformation of HLA-G, it has been recently suggested that this allele could modulate the interaction of HLA-G molecules with the KIR2DL4 receptor on NK cells. 20 Nevertheless, the authors cannot exclude the possibility that the associations found between HLA-G alleles and invasive cancer risk may be the result of linkage disequilibrium with other unknown functional loci. The 3 0 UTR 14-bp polymorphism has been associated with the magnitude of HLA-G production, particularly by modulating HLA-G mRNA stability.…”
Section: Discussionmentioning
confidence: 96%
“…Although it is very unlikely that this amino acid substitution changes the overall conformation of HLA-G, it has been recently suggested that this allele could modulate the interaction of HLA-G molecules with the KIR2DL4 receptor on NK cells. 20 Nevertheless, the authors cannot exclude the possibility that the associations found between HLA-G alleles and invasive cancer risk may be the result of linkage disequilibrium with other unknown functional loci. The 3 0 UTR 14-bp polymorphism has been associated with the magnitude of HLA-G production, particularly by modulating HLA-G mRNA stability.…”
Section: Discussionmentioning
confidence: 96%
“…A familial predisposition to PE has been documented, and both men and women who were the offspring of a pregnancy complicated by PE are significantly more likely to have a pregnancy complicated by PE (Esplin et al, 2001). Although a genetic susceptibility to PE has been established with both maternal and fetal genes and a number of association studies have been performed, the results are inconsistent, and the causative genes involved in PE have yet to be identified (He et al, 2009;Tan et al, 2009).…”
Section: Introductionmentioning
confidence: 87%
“…However, simultaneous activation of the activating isoform of KIR on NK cells can prevent the inhibition of NK cells and mediate proper trophoblast invasion [18]. Pregnant women with fetus carrying the +14/+14 HLA-G genotype or gene-to-gene interaction between fetal HLA-G and maternal KIR2DL4 in multigravid pregnancy may predispose women to PE [19, 20]. Endoplasmic reticulum aminopeptidase 2 (ERAP2) regulates blood pressure (BP) and cytokine production in Norm-Preg.…”
Section: Introductionmentioning
confidence: 99%